Rethingking Pendidikan Islam Antiradikal dan Kejahatan Siber Melalui Program Benchmarking Literasi - Rizki, Azrul; Iqbal, Muhammad (Al Mabhats : Jurnal Penelitian Sosial Agama, 2020)
Through rethingking and civilizing digital soft literacy (pesantren), pesantren are believed to be able to unravel the symptoms of religious radicalism and cyber crime in an increasingly strong virtual space. Literacy benchmarking program is able to parse the symptoms of religious radicalism and cyber crime in virtual space through (1) the habituation stage through reading non-learning books for 15 minutes before learning begins; (2) the development stage includes literacy olympics, peaceful literacy and sharing, literacy creations, silent literacy, social literacy, literacy actions, literacy exhibitions, literacy corners, literacy contributions, literacy discussions, and literacy awards; learning phase, namely the stage to understand the term "world crime" which can be interpreted as something that is destructive; and (3) evaluation stages of all phases that have been carried out in order to obtain follow-up and improvement of the following year's benchmarking programs. The results of the implementation of the literacy benchmarking program at the Integrated Islamic Boarding School Nurul Huda are able to create diversity, strength, and progress of the nation in facing challenges that arise in the era of globalization. This program is able to instill the values of moderate education, tolerance, peace, strengthening friendships, fraternity and compassion so that harmony can be created. With this capital, students can build a country with various achievements.